Characterization of embedded microheater of a CMOS–MEMS gravimetric sensor device. (September 2016) - Dennis, John Ojur; Rabih, Almur A.S.; Md Khir, Mohd Haris; Ahmed, Abdelaziz Yousif; Ahmed, Mawahib Gafare; Mian, Muhammad Umer
Abstract: A CMOS–MEMS device for mass detection has been designed using 2008 CoventorWare software and fabricated using 0.35 µm CMOS technology. This paper reports the characterization of the microheater and the temperature sensor embedded in the device. The measured resistances of the microheater and the temperature sensor were found to be close to the modeled values within ~4.2% error. The average temperature coefficient of resistance (TCR) of the temperature sensor of five dies was determined by increasing or decreasing the temperature in a range of 25 °C–100 °C. The resistance of the temperature sensor was found to increase with either an increase in ambient temperature or the voltage applied to the microheater, with a correlation factor of 0.99. The average TCR was found to be 0.0034/°C for the increasing temperature and 0.0036/°C for the decreasing temperature as compared to 0.0037 °C reported in the literature, indicating an error of 8.1% and 3.5%, respectively. These differences between the measured and reported values are believed to be due to fabrication tolerances in the design dimensions or the material properties. The humidity was found to have a negligible effect on the resistance of the temperature sensor for increasing humidity levels from 40% to 90%. The repeatability of the measurements has shown low standard errors, which gives confidence in the reliability of the fabricated device.